A rare combination of endocrinopathies associated with Camurati-Engelmann disease. - Ooi, Cheow Peng; Mustafa, Norlaila; Abd Wahab, Norasyikin; Zainudin, Suehazlyn; Kamaruddin, Nor Azmi (Elmer Press, 2013)
A case report of a patient with the rare autosomal dominant Camurati-Engelmann Disease (CED) associated with primary hypothyroidism, hypogonadotrophic hypogonadism and central diabetes insipidus is discussed. A thirty-five year old female with CED followed up for the past 27 years in our institution has pathognomonic musculo-skeletal features and multiple endocrinopathies. The clinical history, examination, ultrasound and laboratory investigations over the 27 years were evaluated.